Exploring Partnerships between Academia and Disabled Persons' Organisations: Lessons Learned from Collaborative Research in Africa. (May 2019) - Kett, Maria; Carew, Mark T.; Asiimwe, John-Bosco; Bwalya, Richard; Gitonga, Anderson; Nyehn, Boakai A.; Olenja, Joyce; Swartz, Leslie; Groce, Nora
No abstract available